Formation of Ultra‐Depleted Mantle Peridotites and Their Relationship With Boninitic Melts: An Example From the Kamuikotan Unit, Hokkaido, Japan. Issue 2 (10th February 2023) - Nishio, I.; Morishita, T.; Tamura, A.; Itano, K.; Takamizawa, S.; Ichiyama, Y.; Arai, S.; Barrett, N.; Szilas, K.
Abstract: The extent of partial melting of peridotites is a function of temperature, pressure, and fluid supply. Understanding the petrogenesis of ultra‐depleted peridotites is important for elucidating mantle potential temperature and the role of water in the mantle. We analyzed the major and trace element compositions of ultra‐depleted peridotites from the Kamuikotan zone, Japan. Geochemical models were then generated to constrain the melting conditions and their relation to boninitic melts. The peridotites are characterized by minerals with high Mg/Fe and Cr/Al ratios, and olivine and orthopyroxene with low Ti and Y contents. The mineral compositions suggest that these peridotites are among the most depleted peridotites on Earth. Orthopyroxene compositions characterized by Zr and Sr enrichments relative to Ti and Y depletion cannot be solely explained by melt extraction from typical mantle compositions. Modeling of influx melting reproduces orthopyroxene trace element compositions of ultra‐depleted harzburgites formed after high degrees (>30%) of slab‐fluid influx melting at a low influx rate and melt fraction. The instantaneous fractional melts equilibrated with residues produced by the melting model and the melts, which equilibrated with amphiboles have similar trace elements patterns as boninites. However, the instantaneous fractional melts have low trace element abundances indicating that ultra‐depleted harzburgites are residues after extraction of refractory melts. Boninites are probably accumulated melts formed during the melting processes, or fractionated melt from the instantaneous fractional melts. High temperatures (>1350°C) and continuous fluid supply are key to the formation of ultra‐depleted peridotites and boninites during subduction initiation. Plain Language Summary: Peridotites are the main component of Earth's upper mantle. In the mantle, peridotites undergo a process of partial melting, producing a melt that is "extracted" from original peridotite. When large amounts of melt are extracted from the original peridotite, and is lost to the overlying crust, it leaves behind a peridotite residue which is "ultra‐depleted." Understanding how ultra‐depleted peridotites form is important for elucidating mantle temperatures and the role of fluids such as water in the mantle. We analyzed the chemical compositions of ultra‐depleted peridotites from Japan and conducted geochemical modeling to constrain their formation and relation to subduction initiation. Our geochemical models suggest that these peridotites are among the most depleted peridotites on Earth, most commonly observed in subduction zone environments. We conclude that melting occurred under hydrous, and high temperature (>1350°C) conditions with continuous fluid supply, which is key to the formation of ultra‐depleted peridotites during subduction initiation. Key Points: Harzburgites from the Kamuikotan tectonic belt are among the most depleted peridotites on Earth Ultra‐depleted peridotites formed by high degrees of partial melting as a result of slab‐fluid fluxing High temperatures and fluid supply are key to the formation of ultra‐depleted peridotites and boninites during subduction initiation